A polarization-insensitive dual-band plasmonic metamaterial absorber for a sensor application. (26th March 2021) - Kang, Yongqiang; Gao, Peng; Liu, Hongmei; Gao, Lishuo
Abstract: A polarization-insensitive dual-band plasmonic metamaterial absorber is proposed, which is constituted by merely the metal nano-cylinder and a continuous metallic ground separated by a middle dielectric layer. Two resonance peaks with over 97% absorbance derived from 'the fundamental resonance and the surface lattice resonance are realized. The effective medium approach and the transmission line modeling show good agreement with results from numerical simulation. In addition, we demonstrated that proposed dual-absorber retain nearly perfect absorbance for all polarization angles of both TE and TM modes on normal incidence. It is different from previous work that the dual-frequency response is obtained by combining two subunits of different sizes. Importantly, the second absorption peak result from surface lattice resonance with narrow line-width has large sensitivity perform and high quality factor, which has significant potential in the application of biosensors and monitoring.